A clinical system integration methodology for bio-sensory technology with Cloud architecture - Garai, Ábel; Péntek, István; Adamkó, Attila; Németh, Ágnes (Acta Cybernetica, 2017)
Here, we outline the design, implementation, testing and evaluation phases of our bi-directional semantic and syntactic interoperability framework interconnecting traditional healthcare, industrial telemedicine and IoT wearable eHealth-domains. Specifically, our study demonstrates system interoperability among a hospital information system, an industrial telemedicine instrument and an eHealth smart wearable consumer electronic product through the Open Telemedicine Interoperability Hub (OTI-Hub) embedded in a hybrid Cloud architecture. The novelty of this study is the handling of Internet-ofThingssmart healthcare devices and traditional healthcare devices through the same Cloud-based solution. This healthcare interoperability solution, service architecture and corresponding software engineering technique bridges technology barriers among the above-mentioned healthcare segments. Standard interoperability solutions exist and have already been described in related literature, but they are not applicable to the IoT healthcare devices and vice versa. Our study goes beyond isolated, individual interoperability solutions and seeks to bridge all major healthcare architecture frameworks including classical, telemedicine and eHealth IoT applications and appliances.This study presents the results of a two-year OTI-Hub Research Program. These experiments are manifestations of a trilateral cooperation among the University of Debrecen, Faculty of Informatics, the Semmelweis University 2nd Department of Paediatrics Pulmonology Division and an international hospital information system service provider.